Initial evaluation of nitrogen uptake of Thalassia hemprichii in Nha Trang, Khanh Hoa - Thu, Phan Minh; Hieu, Nguyen Minh; Du, Hoang Trung; Hanh, Nguyen Kim; Mien, Pham Thi; Thi, Vo Hai; Dung], [Le Tran; Hieu, Nguyen Trinh Duc (Vietnam Journal of Marine Science and Technology, 2020)
The uptake rate of nitrate by leaves and roots was simultaneously investigated in the seagrass T. hemprichii collected from Lo river, Nha Trang. The principle of nutrient uptake of seagrass was based on the approaches of the Michaelis-Menten model. The laboratory experiments of nitrate uptake were done the ranges of ambient nitrate concentrations in the separate water column of leaves and roots. The calculated results indicated that the nitrate uptake rate through the leaves was higher than that of the roots. The maximum uptake rate (Vmax) through the leaves and the roots was 1,777.0 mgN/g DW/h and 131.6 mgN/g DW/h, respectively. From these results, the nitrate uptake rate by the seagrass in Lo river was estimated at 52.2 mgNm-2h-1. The value plays an important role in developing and implementing plans for the protection and rehabilitation of seagrass beds in coastal areas.